2019
DOI: 10.1142/s0192415x19500071
|View full text |Cite
|
Sign up to set email alerts
|

Rhein, An Anthraquinone Drug, Suppresses the NLRP3 Inflammasome and Macrophage Activation in Urate Crystal-Induced Gouty Inflammation

Abstract: Rhein, an anthraquinone drug, is a widely used traditional Chinese medicine. Rhein is a major bioactive metabolite of diacerein which has been approved for treating osteoarthritis with a good safety profile in humans. Gouty arthritis is an inflammatory disease characterized by urate crystal-induced NLRP3 inflammasome activation with up-regulated caspase-1 protease and IL-1[Formula: see text] in macrophages. Inhibition of the NLRP3 inflammasome formation has been considered as a potential therapeutic avenue for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Chang et al [26] evaluated the anti-inflammatory activities of rhein on GA and found that it significantly decreases IL-1β production induced by urate crystal by interrupting NLRP3 formation and suppressing caspase 1 (CASP1) protease activity within the physiological levels. In addition, rhein inhibits the transport activity of the renal organic anion transporter (OAT), resulting in the reduction of uric acid re-uptake.…”
Section: The Effects Of Rhein On Gouty Arthritis (Ga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al [26] evaluated the anti-inflammatory activities of rhein on GA and found that it significantly decreases IL-1β production induced by urate crystal by interrupting NLRP3 formation and suppressing caspase 1 (CASP1) protease activity within the physiological levels. In addition, rhein inhibits the transport activity of the renal organic anion transporter (OAT), resulting in the reduction of uric acid re-uptake.…”
Section: The Effects Of Rhein On Gouty Arthritis (Ga)mentioning
confidence: 99%
“…Medicinal plants play a vital role as sources of active anti-inflammatory ingredients in the prevention of various inflammatory diseases. Rhein, a bioactive constituent of anthraquinone, has been well recognized for its excellent anti-inflammatory activities and therapeutic effects on arthritis [26]. A growing body of researches have demonstrated that rhein exhibits anti-inflammatory activities by inhibiting cytokines [27,28] and interleukins [29] which cause inflammatory responses and metabolic abnormalities, stimulates the formation of cartilage matrix material and promotes cartilage repair to remodel joint structures [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[ 82 ] Rhein interfered with the formation of NLRP3 inflammasome by inhibiting caspase‐1 protease activity and IL‐1β production, which suggested that rhein has therapeutic potential for treating NLRP3 inflammasome‐mediated diseases. [ 83 ]…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
“…MAPK14, EGFR, EERB2, TNFRSF1A, etc., are the main targets of the anti-in ammatory effects of rhein. Rhein can directly act on EGFR, MAPK14, EERB2, and TNFRSF1A and can also indirectly act on other targets to exert its anti-in ammatory effects [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%